2022
DOI: 10.1002/rth2.12751
|View full text |Cite
|
Sign up to set email alerts
|

Reduced platelet function in preterm neonates compared with term neonates

Abstract: Essentials• Reduced platelet function might contribute to the longer bleeding time seen in preterm neonates.• Previous studies in preterm neonatal platelet function weeks after birth show variable results.• Platelet count in preterm neonates exceeds term levels 7 weeks after birth.• Platelet activation in preterm neonates remains reduced 7 weeks after birth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
(157 reference statements)
0
2
0
Order By: Relevance
“…In addition, neonatal platelets were found to be hyperresponsive to the platelet inhibitor PGE1, also contributing to the reduced responsiveness. 31 , 33 , 34 , 35 More recent studies have shown distinct platelet hyporeactivity upon immunoreceptor and GPCR stimulation 36 , 37 and have discussed reduced G 12 /G 13 expression as a causative factor for reduced δ-granule secretion. 38 These controversial findings could be explained by the heterogeneous study design regarding readouts (granule release, GPIIb/IIIa activation, aggregometry, and electron microscopy), the material used (peripheral vs umbilical blood), time points, or the respective control group (adults vs infants).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, neonatal platelets were found to be hyperresponsive to the platelet inhibitor PGE1, also contributing to the reduced responsiveness. 31 , 33 , 34 , 35 More recent studies have shown distinct platelet hyporeactivity upon immunoreceptor and GPCR stimulation 36 , 37 and have discussed reduced G 12 /G 13 expression as a causative factor for reduced δ-granule secretion. 38 These controversial findings could be explained by the heterogeneous study design regarding readouts (granule release, GPIIb/IIIa activation, aggregometry, and electron microscopy), the material used (peripheral vs umbilical blood), time points, or the respective control group (adults vs infants).…”
Section: Discussionmentioning
confidence: 99%
“…102,117,118 Neonatal platelets have distinct in vitro patterns of reactivity when compared to adult platelets but are generally hyporeactive to many activating agonists in vitro. [69][70][71][72][119][120][121][122] Although this might suggest that neonates are at greater bleeding risk compared to adults, reduced platelet reactivity is offset in vivo by compensatory hemostatic mechanisms such as higher hematocrit and circulating von Willebrand Factor levels resulting in a net effect of enhanced primary hemostasis compared to adults. It is unclear whether there is an association between 'adult' platelet transfusions in neonates and thrombosis, as there are currently no robust datasets available to assess this.…”
Section: Specification and Administration Of Platelet Componentsmentioning
confidence: 99%
“…42 The past three decades have seen considerable advances in flow cytometry analysis, platelet activation analyses, and further characterization of platelets signaling pathways, as summarized by Ramström et al 42 The analysis uses only a small sample volume which makes investigations possible even in premature newborns. 43 However, the analysis is highly specialized, requires highly skilled technicians, and the subsequent interpretation of results is also demanding. Researchers of today are still working to develop flow cytometry for platelet investigations and to standardize the analysis.…”
Section: Platelet Activationmentioning
confidence: 99%